Hydrogel plus growth factors treatment after 2940nm erbium:YAG lattice laser improves periorbital wrinkles and wound healing: a case report. Issue 9 (September 2021) - Zeng, Jiaqi; Li, Zhen; Lin, Feiyan; Fu, Shaohong; Li, Jingyi; Zhai, Yabin
Skin aging is an inevitable physiological process and periorbital wrinkling is an active sign of the process. Laser therapy is an effective method for improving periorbital wrinkles and wound care after laser therapy can accelerate the wound healing process. This case report describes a typical case of a 47-year-old male that presented with a 10-year history of gradually-worsening bilateral periorbital wrinkles. These were treated using a 2940 nm erbium (Er):YAG lattice laser combined with recombinant bovine basic fibroblast growth factor (bFGF) gel and hydrogel (HG) treatment on the left side of his face compared with laser therapy and bFGF gel on the right side of his face. HG combined with bFGF gel treatment after 2940 nm Er:YAG lattice laser therapy improved postoperative swelling and pigmentation compared with bFGF gel alone; and it promoted periorbital wrinkle improvement and wound healing. In conclusion, HG combined with GFs after laser therapy could be an alternative therapy for periorbital wrinkles.